As práticas terapêuticas não convencionais nos serviços de saúde: revisão sistemática da literatura - Cruz, Pérola Liciane Baptista da (2013)
Introduction: Based in proposed changes in the health care model, aiming at complying the principles of Unified Health System, and enhanced by international bodies such as World Health Organization, the use of integrative practices have increased in the services of health care in Brazil. In the case of traditional medicine or complementary and alternative system, the primary health care has become the main focus of action globally, with several benefits brought across studies. With the large number of information related to the issue, aimed to review the literature indexed in databases the search for scientific evidence concerning in the period between 2006 and 2012. Methods: The integrative literature review enables the synthesis of the state of knowledge of a subject, occurring in six stages: identifying the topic, literature search, categorization of studies, evaluation studies, interpretation of results and presentation of the synthesis. Results: Selected 42 studies for analysis, present a strong presence of traditional practices in the field of primary care globally, and experiences the use of alternative and complementary medicine, outside Brazil, in tertiary care setting. It is observed lack of knowledge of professionals and shortages public policies for real theme development, as well as further evidence about the costs of this change in the way health care. Conclusion: Based on the benefits already identified and discussed, the comprehensive improvement in the quality of life in communities, points to the need for greater investment in research, dissemination and training in the area, in order to supply an increasing demand, as well as studies that brings evidence to safety use and public investments.